Implementasi Akad Murabahah pada Pembiayaan Mikro (Studi Bank Syariah Indonesia Kantor Cabang Pangkalpinang) - Hasanah, Anik Uswatun; Irvani, Ahmad; Nurdin, Muhamad (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2024)
This research raises the problem of murabahah using wakalah contracts in murabahah transactions because side streaming often occurs by customers after disbursement of murabahah financing. This research aims to analyze how murabahah contracts are implemented and analyze how murabahah contracts are monitored in micro financing. Study of Bank Syariah Indonesia Pangkalpinang Branch Office. BSI applies murabahah financing products which are applied to micro financing which aims to enable members to own goods or business equipment to support business activities. The type of research used is qualitative descriptive research using primary data and secondary data. Data collection techniques through observation, interviews, documentation. Respondents were bank leaders, micro marketing staff and operational staff. As for the data analysis method using the Miles and Huberman approach, namely data reduction, data presentation, and drawing conclusions. The results of this research show that in theory the murabahah bil wakalah contract carried out by BSI KC Pangkalpinang in financing micro businesses is in accordance with the DSN-MUI fatwa. The murabahah process with wakalah is to carry out a wakalah contract first. After that, enter into a murabahah contract. Murabahah which is applied to micro financing using murabahah bil wakalah often causes side streaming by customers when the bank is disbursed with a wakalah agreement.